Exploring the Role of Self-Control on Student Procrastination - Hariz Enggar Wijaya; Arief Rahman Tori (Universitas Negeri Padang, 2018)
Procrastination is widespread across the nation and setting. Its occur commonly in an academic setting which has many demands and deadline. One of the variable construct which reported has a high association with procrastination is self-control. It is why we would like to find out the role of self-control on student procrastination. There were 100 undergraduate students enrolled this study, from religious education faculty of a private university in Yogyakarta. Pure Procrastination Scale, Procrastination Academic Scale for Student, and Brief Self-Control Scale were administered to obtain student procrastination and self-control. Results showed that self-control correlates moderately negative with both of general and academic procrastination. Also, self-control could predict procrastination both in an academic and general setting. As an additional, there were significantly different between the lowest and highest procrastination group based on student self-control, with big size-effect reported. For further analysis, the prevalence of six areas of academic procrastination also discuss.